Psychotherapeutic interventions for the prevention of suicide re-attempts: a systematic review. Issue 15 (5th November 2021) - Sobanski, Thomas; Josfeld, Sebastian; Peikert, Gregor; Wagner, Gerd
Abstract: A history of suicide attempt (SA) is a strong predictor of future suicide re-attempts or suicide. The aim of this systematic review is to evaluate the efficacy of psychotherapeutic interventions specifically designed for the prevention of suicide re-attempts. A systematic search from 1980 to June 2020 was performed via the databases PubMed and Google Scholar. Only randomized controlled trials were included which clearly differentiated suicidal self-harm from non-suicidal self-injury in terms of intent to die. Moreover, psychotherapeutic interventions had to be focused on suicidal behaviour and the numbers of suicide re-attempts had to be used as outcome variables. By this procedure, 18 studies were identified. Statistical comparison of all studies revealed that psychotherapeutic interventions in general were significantly more efficacious than control conditions in reducing the risk of future suicidal behaviour nearly by a third. Separate analyses revealed that cognitive-behavioural therapy as well as two different psychodynamic approaches were significantly more efficacious than control conditions. Dialectical behaviour therapy and elementary problem-solving therapy were not superior to control conditions in reducing the number of SAs. However, methodological reasons may explain to some extent these negative results. Considering the great significance of suicidal behaviour, there is unquestionably an urgent need for further development of psychotherapeutic techniques for the prevention of suicide re-attempts. Based on the encouraging results of this systematic review, it can be assumed that laying the focus on suicidal episodes might be the key intervention for preventing suicide re-attempts and suicides.